2001
DOI: 10.2307/3079159
|View full text |Cite
|
Sign up to set email alerts
|

Shared Preferences by Predators and Females for Male Ornaments in Swordtails

Abstract: Sexually dimorphic traits in many mate recognition systems have evolved in response to preexisting female biases. These biases are often quite general in form and are likely to be shared by predators, thereby imposing a cost on male trait expression. The Mexican tetra Astyanax mexicanus (Pisces: Characidae), a visual predator of swordtail fishes, exhibits the same visual preferences for male body size morphs as do females. Furthermore, tetras in populations where swordtails are absent prefer males with sword o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 20 publications
3
52
0
Order By: Relevance
“…Many components of male sexual signals that are preferred by females are also those most attractive to predators (Rosenthal et al 2001), and female mate choice can be sensitive to such predation risks; females may mate randomly or with less-preferred males when the predation risks of responding to preferred male signals are high (e.g. Hedrick and Dill 1993;Grafe 1997).…”
mentioning
confidence: 99%
“…Many components of male sexual signals that are preferred by females are also those most attractive to predators (Rosenthal et al 2001), and female mate choice can be sensitive to such predation risks; females may mate randomly or with less-preferred males when the predation risks of responding to preferred male signals are high (e.g. Hedrick and Dill 1993;Grafe 1997).…”
mentioning
confidence: 99%
“…The relatively shorter sword of males captured in the field may suggest that the wild population is composed mainly of younger males than the ones reared in this study. Our results show that the sword continues growing with age, which is accompanied by the increasing energetic cost of swimming (Basolo and Alcaraz 2003), and possibly higher predation risk (Rosenthal et al 2001). Thus, the increase in sword length through life may play an important role in male survival, making it costly for males in the wild to have long swords.…”
Section: Discussionmentioning
confidence: 71%
“…However, maturation in this species, as in other swordtails (Xiphophorus nigrensis, Ryan et al 1992;Xiphophorus helleri, Basolo 2008), may be costly in terms of the decrease in both growth rate and size at maturity. Additionally, in swordtails, maturation is also accompanied by increasing fitness costs associated with the sword: energetic costs of swimming (Basolo and Alcaraz 2003), reduced swimming velocity (Kruesi and Alcaraz 2007), and increased predation risk (Rosenthal et al 2001). Several lines of evidence suggest that sexual selection favoring sword elongation is counterbalanced by natural selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, males may have a reduced survival compared with females due to increased conspicuousness and not due to a reduction in locomotor performance. In fact, studies have demonstrated a repeated correlation of sword reduction with the presence of predators (Basolo and Wagner 2004) and that females as well as predators prefer males with longer swords (Rosenthal et al 2001). Costs may also occur through increased metabolic demands throughout life and via shorter life spans in males with longer swords.…”
Section: Discussionmentioning
confidence: 99%